Evaluation of different vagus nerve stimulation anatomical targets in the ear by vagus evoked potential responses. Issue 11 (22nd September 2021) - de Gurtubay, Iñaki Garcia; Bermejo, Pedro; Lopez, Miguel; Larraya, Iñaki; Librero, Julian
Abstract: Background: Electrical auricular vagus nerve stimulation (taVNS) is an emerging therapy. Stimuli are transported to brainstem nuclei, whereby its multiple projections reach to many subcortical and cortical areas, thus allowing the neuromodulation of several systemic physiological processes. We aim to define the best auricular target for taVNS through vagus somatosensory evoked potential (VSEP) elicited stimulating different auricular areas with different electrode sizes. Methods: Twenty‐six subjects were enrolled. Three stimulation areas were studied: simultaneous cymba and cavum (CC), cymba (C) and earlobe (L); and two electrode sizes: extra‐large (X) and small (S). We studied the effect of five combinations (CCX, CCS, CS, LX and LS) on VSEP´s latency and amplitude, and sensory and pain threshold (Pt) using a lineal mixed model regression analysis. We used CS combination, used in a commercial device, as reference model. Results: Valid VSEP were obtained for CCX, CCS and CS but not in LX and LS. Both CCS and CCX tests showed significant amplitude increases. The same effect was observed in CCX using CCS as reference. Significant increases in Pt were found for CCX and LX. The same effect was observed in CCX using LX as reference. Conclusion: The results suggest that CC and C areas are active targets for taVNS but not for earlobe, as anatomical data support. Considering that amplitude reflects the synchronized electrical activity generated, we conclude the most effective topography is the simultaneous stimulation of cymba and concha. The use of X‐sized electrodes increases the amplitudes and makes the stimulation more comfortable. Abstract : Electrical auricular vagus nerve stimulation (taVNS) is an emerging therapy. Stimuli are transported to brainstem nuclei, whereby its multiple projections reach to many subcortical and cortical areas, thus allowing the neuromodulation of several systemic physiological processes. We aim to define the best auricular target for taVNS through vagus somatosensory evoked potential (VSEP) elicited stimulating different auricular areas with different electrode sizes.